a Strategıes To Improve Fınancıal Lıteracy Through Behavıor: Predıctors Of Fınancıal Well-Beıng Of Indonesıan Malang Creatıve Craft Industry Exporters - Ratnawati Ratnawati; Ayu Agus Tya Ningsih (Cita Konsultindo Research Center, 2024)
Small and Medium Industries in the export handicraft sector make a major contribution to increasing national income and regional income so that financial welfare is an important thing to pay attention to by the relevant agencies and institutions. This research aims to test and analyze the influence of financial literacy on the financial welfare of SME owners in the craft sector mediated by financial behavior. The research that will be carried out is (Explanatory). The analytical tool used as a mediation test is the Structural Equation Model with Sobel. The research results provide the meaning that financial literacy influences financial behavior. The financial behavior of small and medium industry players or MSMEs has a direct influence on financial well-being. Financial behavior can mediate the influence of financial literacy on the financial welfare of small and medium industry players or MSMEs.